Mulla Sadra dan Transendensi Diri - Dwi Pratomo (ILMU USHULUDDIN, 2017)
Existentialism is indeed a very loose term, Sartre once state this in his famous lecture. But Sartre was saying how people use the term existentialism in his own age and culture. The problem would become more complex if we, instead of attributing this term to Sartre, Heidegger and another so-called modern existentialist philosopher, state that Mulla Sadra, a contemporary of Descartes, is also an existentialist philosopher, yes, he too, advocating the primacy of existence over essence. Despite much problems concerning technical vocabulary and the separate horizon wherein each existentialist philosopher dwell (i.e Sadra and Sartre), there is at least a similar problem that concern themselves. Particularly, as we will explore in this article, the problem of the self. Technical vocabulary and historico-spiritual horizon aside, there is an interesting intersection between the two's conception of the Self. Sartre explore the problem of the self in his Transcendence of the Ego, while Sadra here is only assumed.